Clinical pharmacokinetics of methotrexate in the treatment of acute lymphoblastic leukemia and non-Hodgkin lymphoma in pediatric patients - Škorić Biljana; Jovanović Marija; Miljković Branislava; Kuzmanović Miloš; Vučićević Katarina (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2020)
High dose methotrexate (MTX) is used in therapy of acute lymphoblastic leukemia and non-Hodgkin lymphoma in pediatric patients. It acts as competitive inhibitor of dihydrofolate reductase and consequently inhibits synthesis of deoxyribonucleic acid. The bioavailability is dependent upon dose and route of administration. The drug is moderately bound to plasma proteins and distributes in body tissues and cells. After the administration in high doses, MTX partially undergoes hepatic and intracellular metabolism, but renal excretion of parent compound is the main route of elimination. Numerous factors may influence pharmacokinetics and concentration of drug, but primarily the effect of renal function on elimination is described. Delayed elimination might also be the consequence of drug interaction in renal tubules. Toxicity can arise with high MTX doses, especially in patients with delayed MTX elimination. Therapeutic drug monitoring is indicated due to safety reasons, in order to optimize leucovorin (folinic acid) administration as it reduces MTX toxicity. Considering the variability and the toxicity of high dose MTX therapy, special caution is required in pediatric patients.